Innovating Mathematics Learning through Augmented Reality and Deep Learning: A Needs Analysis on Functions Concept Learning - Maman Suryaman; Mujiyem Sapti; Hermawan Hermawan (FKIP - Universitas Riau, 2026)
Learning about relationships and properties of functions in secondary schools is still predominantly procedural, limiting students' conceptual understanding. This study aimed to analyze the need for developing Augmented Reality (AR) learning media integrated with a deep learning approach to strengthen students' conceptual understanding of relationships and properties of functions. A descriptive study with a mixed methods approach was employed, combining questionnaire and interview data from 39 high school mathematics teachers (13 from Merangin Regency, Jambi, and 26 from Purworejo Regency, Central Java). Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed thematically. The findings revealed that students continue to experience difficulties in general concept understanding (26%), specific concepts understanding (62%), and application skills (33%). Teachers also reported that existing learning media is insufficient for visualizing abstract mathematical concepts interactively. Although the implementation of AR remains limited, teachers expressed positive perceptions of its potential and emphasized the need for learning media featuring three-dimensional visualization, interactive simulations, contextual examples, and adaptive learning activities. These findings provide a strong empirical basis for the design and development of AR-based learning media and confirm that this study represents the needs analysis stage, which will inform subsequent media development and validation.